'I am not being sponsored to say this': a teen youtuber and her audience negatiate branded content - Jorge, Ana; Marôpo, Lidia; Nunes, Thays (Instituto Universitário de Lisboa, ISCTE, 2018)
The field of microcelebrity is increasingly monetised, professionalised, and institutionalised, with the growing recognition of content creators as social media influencers. This article looks at the integration of branded content within youth digital culture, where participatory possibilities for self-expression are more and more entwined with consumer culture. It seeks to discuss how digital producers understand brand culture and how audiences negotiate the meanings of the commercialism inserted in their content. We look at the case of SofiaBBeauty, a successful young Portuguese youtuber, who has been vlogging since she was 12. The article analyses her association with brands in 12 videos in 2017 (vlog, haul, giveaway, Q&A, first impression, etc.), and the comments by the users showing acceptance and appraisal of, negotiation, or criticism towards, the brand and/or the youtuber. We explore the way Sofia connects her self-presentation with products/brands to appear close to her young audiences, and brands her persona as she is growing up to adulthood; how she presents her commercial recommendations as genuine and pregnant with affect, and whether the audience accepts it or not; as well as how she positions herself in the global YouTube community of practice, where connection with brands aggrandizes her persona in the eyes of the audience. Sofia’s videos create a post-feminist subject where consumption is articulated with independence, capability, and empowerment (Banet-Weiser, 2011), while engaging her audiences in a commodification process (Berryman & Kavka, 2017).
Keywords: Youth; Audiences; Commercialism; Social media; Microcelebrity; Commodification